DEVELOPING THE GUIDELINES FOR SCHOOL FUND RAISING UNDER THE SECONDARY EDUCATIONAL SERVICE AREA OFFICE 27 - Jomhong, Boonsong; Ruangmontri, Karn (Journal of MCU Nakhondhat, 2020)
This study aimed to: 1) study existing condition, desirable condition and need order of the school fund raising ; 2) developing the guidelines for school fund raising under the Secondary Educational Service Area Office 27. The study consisted of 2 phases: Phase 1 existing condition and desirable condition for school fund raising study by using a questionnaire, and need index analysis; Phase 2 School fund raising guidelines designing. The sample consisted of 387 school directors and teachers selected by porportional stratified random sampling technique accompanied by an interview about school fund raising success with 3 school directors ; and 9 experts for the school fund raising guidelines development for Phase 2. The tools for this study were 5 – rated scale questionnaire, interviewing form and suitability and feasibility evaluation form. Percentage, arithmetic means, standard deviation and Priority Needs Index (PNI) was used to analyze the obtained data. The research result were: 1) From the existing condition of school fund raising under the Secondary Educational Service Area Office 27, it was found that there were high average score as a whole. The desirable condition of the school fund raising average score was at highest level as a whole. First priority need was school fund raising planning. 2) The school fund raising guidelines consisted of 4 factors. and 15 guidelines. From school fund raising guideline evaluation, it was found that the guidelines were both high level of suitable and feasible.